A review of the holy Quran listening and its neural correlation for its potential as a psycho-spiritual therapy - Mohammed Abdalla, Kannan; Nurfaizatul Aisyah, Ab Aziz; Nur Syairah, Ab Rani; Mohd Waqiyuddin, Abdullah; Muhammad Hakimi, Mohd Rashid; Mas Syazwanee, Shab; Nurul Iman, Ismail; Muhammad Amiri, Ab Ghani; Faruque, Reza; Mustapha, Muzaimi (Elsevier Ltd., 2022)
Since its revelation over 14 centuries ago, the Holy Quran is considered as scriptural divine words of Islam, and it is believed to promote psycho-spiritual therapeutic benefits to its reciter and/or listener. In this context, the listening of rhythmic Quranic verses among Muslims is often viewed as a form of unconventional melodic vocals, with accompanied anecdotal claims of the ‘Quranic chills’ pleasing effect. However, compared to music, rhythm, and meditation therapy, information on the neural basis of the anecdotal healing effects of the Quran remain largely unexplored. Current studies in this area took the leads from the low-frequency neuronal oscillations (i.e., alpha and theta) as the neural correlates, mainly using electroencephalography (EEG) and/or magnetoencephalography (MEG). In this narrative review, we present and discuss recent work related to these neural correlates and highlight several methodical issues and propose recommendations to progress this emerging transdisciplinary research. Collectively, evidence suggests that listening to rhythmic Quranic verses activates similar brain regions and elicits comparable therapeutic effects reported in music and rhythmic therapy. Notwithstanding, further research are warranted with more concise and standardized study designs to substantiate these findings, and opens avenue for the listening to Quranic verses as an effective complementary psycho-spiritual therapy